PENGAMATAN ERITROSIT DAN LEUKOSIT PADA IKAN GURAMI (Osphronemus gourami) YANG MENERIMA PERLAKUAN TANAMAN HERBAL DAN INFEKSI Mycobacterium fortuitum - Nunaq Nafiqoh; Yudiana Jasmanindar (Nusa Cendana University, 2021)
Disease outbreaks are inseparable from culturing process, preventive and treatment is effective to avoid mass mortality. The aim of this study is to observe the potent of combined herbs to treat Mycobacteriosis. Herbs were sprayed to fish feed with different dose (0%, 0.5%, 1%, and 2%) per kg feed. The observed parameters were erythrocyte and leucocyte count. The result showed, in the end of the experiment there is no significant different on leucocyte count among treatment. While, the highest erythrocyte count was showed by 0.5% treatment group. In the other hand the highest survival rate was showed by 1% treatment group. Key Word : Erytrocyte, Gouramy, Herbs, Leucocyte, Mycobacterium